Self-Care Practices Of Saudi Diabetic Foot Patients In 2024 (The Review of Diabetic Studies, 2024)
Background: Diabetic foot is a foot that shows any pathology that consequence in a straight line from diabetes mellitus or any long -term complications of DM which lead to diabetic foot amputation when delaying in treatment.Aim of the study: Was to assess self-care practices of Saudi diabetic foot patients.Research design: A descriptive research design was utilized to conduct this study.Setting: This study was conducted at Diabetic Patient Clinic of Taif hospital, Saudi Arabia.The sample: A systematic sample of 200 diabetic foot patients over 50 years old.Tools: One tool was used in this study. 1): A structured interviewing questionnaire which consists of four parts.Part (1): Demographic characteristics of diabetic foot patients,Part (2): Medical history of diabetic foot patients. Part (3): Patients’ knowledge about diabetes Mellitus and diabetic foot.Part (4): Diabetic patients’ reported practices toward diabetic foot self- care.Results: 46.5% of studied patients aged from60